2020
DOI: 10.29271/jcpsp.2020.06.638
|View full text |Cite
|
Sign up to set email alerts
|

Acute Side Effects with High Dose Rate Computed Tomography-guided Three-dimensional Brachytherapy in Carcinoma Cervix

Abstract: Objectives: To determine the frequency and grades of acute side effects with three-dimensional brachytherapy in carcinoma cervix using RTOG/EORTC acute radiation morbidity scoring criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…In comparable with a recent study (Sadiq, Shahid et al 2020) stratification of grades of acute side effects with respect to age groups revealed that age was not significantly related with severity of acute toxicities, no significant difference was observed in GU, lower GIT and vaginal toxicities with respect to age .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In comparable with a recent study (Sadiq, Shahid et al 2020) stratification of grades of acute side effects with respect to age groups revealed that age was not significantly related with severity of acute toxicities, no significant difference was observed in GU, lower GIT and vaginal toxicities with respect to age .…”
Section: Discussionsupporting
confidence: 80%
“…In comparable with Koji Matsuo et al (Matsuo, Klar et al 2021) as reported that cervical cancer was (48.1%) with grade 3 tumors, (44.7%) with grade 2 neoplasms and associated with older age, higher stage disease, larger tumor size, and lymph node metastasis. Regarding treatment of 30 patients, received concurrent chemoradiotherapy using weekly platinum based chemotherapy with a dose of 45 Gy in 1.8-2 Gy/fraction followed by brachytherapy years with significant difference <0.001 and patients with HTN, 80% of them had grade 2 toxicity with significant difference 0.007, no significant difference for PS, pathology, grade of tumor and stage with a dose of 7GY/4 Fr except two patient received 7GY/2Fr and 7GY/3Fr due to sever toxcity with prescription dose 7GY, that was similar to Sadia Sadiq, Abubaker Shahid et al (Sadiq, Shahid et al 2020) and EMBRACE-I (Pötter, Tanderup et al 2021).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations